COVID-19 and Inherited Metabolic Disorders: One-Year Experience of a Referral Center - Albina Tummolo; Giulia Paterno; Annamaria Dicintio; Pasquale Stefanizzi; Livio Melpignano; Maurizio Aricò (MDPI AG, 2021)
Understanding the potential risks of patients with inherited metabolic disorder (IMD) exposed to the COVID-19 pandemic is an unmet need for those involved in their management. Here, we report on the incidence of COVID-19 in a cohort of patients with IMD treated at a children's hospital and compare them with a matched control group. Among the total number of 272 patients actively followed at a referral center, 19 (7%) tested positive for SARS-CoV-2 between March 2020 and March 2021. Their median age was 16.2 years (range 1.4-32.8 years). In two-thirds of the cases, the source of infection was a family member; 12/19 patients (63%) were asymptomatic, only one required hospitalization, and none of them died. In our single-center experience, COVID-19 had a moderate impact on a relatively large cohort of patients with IMD, including children and young adults. The clinical course was very mild in all but one case. The proportion of symptomatic cases and the clinical course were comparable in patients with IMD and in a group of matched, non-IMD COVID-19 controls from the general population.